Structure of transmembrane AMPA receptor regulatory protein subunit γ2 - W. Dylan Hale; Alejandra Montaño Romero; Nicholas Koylass; Collin R. Warrick; Zhaozhu Qiu; Richard L. Huganir; Edward C. Twomey (Nature Communications)
Abstract Transmembrane AMPA receptor regulatory proteins (TARPs) are claudin-like proteins that tightly regulate AMPA receptors (AMPARs) and are fundamental for excitatory neurotransmission. With cryo-electron microscopy (cryo-EM) we reconstruct the 36 kDa TARP subunit γ2 to 2.3 Å, which points to structural diversity among TARPs. Our data reveals critical motifs that distinguish TARPs from claudins and define how sequence variations within TARPs differentiate subfamilies and their regulation of AMPARs.